التعاون الاقتصادي العربي ومقومات التكامل الزراعي لتحقيق الأمن الغذائي في الدول العربية: Arab economic cooperation and the pillars of agricultural integration to achieve food security in Arab countries - ملال أحمد; دربال عبد القادر (Journal of North African Economies, 2025)
While the trade liberalization process - under the aegis of the World Trade Organization (WTO), in parallel with the trading blocs - has succeeded in opening up the world trade in agriculture and increasing the intensity of the flow of Agrofood products. At the same time, the weakness that the Arab region faces in the value of agricultural trade has shown the limited extent of Arab economic cooperation and integration, despite their role in stimulating economic growth and their importance in promoting skills development at the regional level, which has contributed to widening the Arab food gap in favor of other partner countries to reach the 33,6 billion limit in 2017, To this end, this research will attempt to analyze the main problems related to the agricultural sector in the Arab countries, in order to identify their common points, challenges and opportunities that can be achieved through a prodigious effort in the field of inter-Arab agricultural cooperation in order to ensure Arab food security, and reduce the still significant food deficit.